Analysis of Temperature Semi-Annual Oscillations (SAO) in the Middle Atmosphere - Ming Shangguan; Wuke Wang (Remote Sensing, 2023)
The middle atmosphere plays an important role in the research of various dynamical and energy processes. Microwave Limb Sounder (MLS), reanalyses and model simulations with NCAR’s Whole Atmosphere Community Climate Model (WACCM) data in the range between 100 and 0.1 hPa from 2005 to 2020 have been analyzed with a focus on the temperature semi-annual oscillations (SAO). Significant SAO of temperature is prominent in the tropical region (20<semantics>°</semantics>S–20<semantics>°</semantics>N) around 1–3 hPa, which is consistent with previous studies. We also found significant SAO in the northern hemisphere (NH) high latitudes between 8 and 0.3 hPa and southern hemisphere (SH) high latitudes between 0.5 and 0.1 hPa, which has been of less concern in previous studies. The thermal budget based on MERRA2 and simulations is used to explain the mechanism of SAO in the middle atmosphere. In the tropics, the two temperature peaks are mainly determined by radiative processes. In the NH high latitudes of the stratosphere, the temperature peak in January is mainly related to dynamical processes, while the temperature peak in July is determined by a combination of dynamical and radiative processes. In the NH high latitudes of the lower mesosphere, the first peak in June is primarily associated with dynamical and radiative processes, while the second peak in December is primarily associated with the dynamical processes. In the SH high latitudes of the lower mesosphere, the first temperature peak in July is mainly due to dynamical processes while the second temperature peak in December is mainly due to radiative processes. Various features are present in the SH and NH high latitude SAO in the lower mesosphere. Furthermore, we performed model simulations with and without SAO in sea surface temperatures (SST-SAO) to study the connection between SST and temperature SAO. WACCM6 results indicate that the SAO in the middle atmosphere is partially affected by the existence of an SST-SAO. By removing SAO in SST, the PSD magnitude of the SAO decreases in the tropical region and increases in the polar region. The amplitudes of total heating rates are also modified. The WACCM experiment confirms the relationship between SST-SAO and temperature SAO in the middle atmosphere.